Low temperature NH3-SCR activity enhancement of antimony promoted vanadia-ceria catalyst - Kumar, Pullur Anil; Jeong, Young Eun; Ha, Heon Phil (ELSEVIER, 2017)
In this work, the antimony promoted Vanadia-Ceria catalysts have been prepared by homogeneous precipitation method for the selective catalytic reduction of NOx with NH3. With an introduction of Sb into Vanadia-Ceria, the catalysts showed an improvement in the low temperature NOx conversion below 250 degrees C. These high activities of the Sb promoted catalysts were related to the increase of acid sites and redox properties of the catalysts, which were investigated by the NH3-TPD (temperature programmed desorption), H-2-TPR (temperature programmed reduction) and in-situ NH3-DRIFTS (diffused reflectance infrared Fourier transformed spectroscopy) spectra. In addition, structural and morphological properties of these catalysts were examined by X-ray diffraction, BET surface area and FE-SEM (Field emission scanning electron microscopy). After the addition of Sb to Vanadia-Ceria, the increase of surface area with a smaller, uniform sized particles and high dispersion of vanadia were indicated in the optimized 4wt.% V2O5-2wt.% Sb-CeO2 catalyst. Furthermore, the Lewis and Bronsted acid sites were enhanced in the 4 wt.% V2O5-2wt.% Sb-CeO2 catalyst to promote NOx conversion at a wide temperature range of 175-400 degrees C. XPS results also indicated an improvement in the active oxygen species of this catalyst due to the enhancement of surface oxidation species of V4+/V5+, Sb3+/Sb5+ and Ce3+/Ce4+. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: V-BASED CATALYST; NO REDUCTION; SCR REACTION; REACTION-MECHANISM; NITRIC-OXIDE; NH3; AMMONIA; REMOVAL; MN; ADSORPTION